Prove the arithmetic progressions equation, Mathematics

Prove that am + n + am - n  =2am

Ans:    a m + n = a1 + (m + n - 1) d

a m-n = a1 + (m - n -1) d

am = a1 + (m-1) d

Add 1 & 2

a m+n + a m-n  =   a1+(m+n-1) d+ a1 + (m-n-1)d

=          2a1+(m+n+m-n-1-1)d

=          2a1+ 2(m-1)d

=          2[a1+ (m-1)d]

=          2[a1+ (m-1)d]

=          2am.       Hence proved.

Posted Date: 4/8/2013 5:30:01 AM | Location : United States







Related Discussions:- Prove the arithmetic progressions equation, Assignment Help, Ask Question on Prove the arithmetic progressions equation, Get Answer, Expert's Help, Prove the arithmetic progressions equation Discussions

Write discussion on Prove the arithmetic progressions equation
Your posts are moderated
Related Questions
more questions on wavy curve method


Game Theory It is used to find out the optimum strategy in a competitive condition,While two or more competitors are engaged in making decisions, this may occupy conflict of in

Explain Combining Negative Signs in integers? You've learned about positive and negative integers. BASICS :   When you place a negative sign in front of an integer, you get

Let's recall how do to do this with a rapid number example.                                                     5/6 - 3/4 In this case we required a common denominator & reme

The Lognormal Distribution If ln(X) is a normally distributed random variable, then X is said to be a lognormal variable. If P1, P2, P3, ... are the prices of a scrip in per

how to find inverse of matrix

Question: Solve the initial value problem 2x'' +x'-x =27 Cos2t +6 Sin 2t, x(0)=2 , x'(0)= -2 by using Laplace transform method.

application of derivatives in engg.

Write an algebraic expression for “Julie runs three miles less than twice the number of miles,